Calidad de vida y apoyo social en mujeres con cáncer de mama - Sandra Milena Martínez Rojas (Universidad Francisco de Paula Santander, 2018)
Objective: To establish the relationship between quality and social support in women diagnosed with breast cancer that chemotherapy treatment in the cancer clinic of Norte de Santander. Materials and Methods: Correlational quantitative study, of transversal descriptive type, in which a sample of 120 women was calculated, with a selection of intentional convenience. The collection of the information was done through the instruments of QOL of Betty Ferrell and (SSCI) of G. Hilbert where the quality of life and social support of this group of women was established. Results: A quality-life relationship was presented in the dimensions that most correlated with the physical and the psychological, likewise, social support was obtained from the people around them, evidencing the signifi cant relationship of all the dimensions among themselves. Conclusion: the relationship between quality of life and social support in women with breast cancer and treatment with chemotherapy, accepts the hypothesis that there is no correlation between the variables, although the p value, = 0.002 represents a statistical signifi cance, It follows that the two variables, although independent, are related to each other by the dimensions and subscales.